Two new species of Calanthe (Orchidaceae: Epidendroideae) from Korea - Oh, Sang-Hun; Suh, Hwa-Jung; Park, Chong-Wook (Phytotaxa, 2015)
Two new species, Calanthe insularis S.H.Oh, H.J.Suh & C.-W.Park and Calanthe rubra S.H.Oh, H.J.Suh & C.-W.Park, are described, illustrated, and compared with closely related species. Calanthe insularis, distributed in the southwestern region of Korea and Tsushima Island in Japan, is morphologically similar to C. aristulifera and C. striata, but it is distinguished from the last two species in its creamy yellow and pale orange-yellow flowers, arcuate spur as long as the lip, pale orange-yellow pedicels, and green ovary with pale green ridges. Calanthe rubra, from Gageodo Island, Korea, is similar to C. striata and C. insularis, but differs from them in its much smaller flowers with purplish red sepals and petals and the white spur.